2021
DOI: 10.1093/nar/gkab872
|View full text |Cite
|
Sign up to set email alerts
|

A standard knockout procedure alters expression of adjacent loci at the translational level

Abstract: The Saccharomyces cerevisiae gene deletion collection is widely used for functional gene annotation and genetic interaction analyses. However, the standard G418-resistance cassette used to produce knockout mutants delivers strong regulatory elements into the target genetic loci. To date, its side effects on the expression of neighboring genes have never been systematically assessed. Here, using ribosome profiling data, RT-qPCR, and reporter expression, we investigated perturbations induced by the KanMX module.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…In this study, we provide evidence that genome-inserted expression cassettes drive bidirectional transcription and the production of divergent transcripts that can repress neighboring genes in yeast, resulting in potent off-target effects, even in carefully designed single-gene studies. Our data also provide a mechanism for the mysterious NGE, identified in analyses of yeast deletion collection studies, and clarify why some loci are susceptible to off-target effects, while some are immune ( Ben-Shitrit et al, 2012 ; Atias et al, 2016 ; Egorov et al, 2021 ; Makeeva et al, 2019 ). We find that expression cassette insertion at DBP1 reduces the translation of neighboring gene MRP51 through a divergent LUTI driven by the bidirectional activity of cassette promoters ( Neil et al, 2009 ; Xu et al, 2009 ; Churchman and Weissman, 2011 ).…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…In this study, we provide evidence that genome-inserted expression cassettes drive bidirectional transcription and the production of divergent transcripts that can repress neighboring genes in yeast, resulting in potent off-target effects, even in carefully designed single-gene studies. Our data also provide a mechanism for the mysterious NGE, identified in analyses of yeast deletion collection studies, and clarify why some loci are susceptible to off-target effects, while some are immune ( Ben-Shitrit et al, 2012 ; Atias et al, 2016 ; Egorov et al, 2021 ; Makeeva et al, 2019 ). We find that expression cassette insertion at DBP1 reduces the translation of neighboring gene MRP51 through a divergent LUTI driven by the bidirectional activity of cassette promoters ( Neil et al, 2009 ; Xu et al, 2009 ; Churchman and Weissman, 2011 ).…”
Section: Discussionmentioning
confidence: 55%
“…We conclude that resistance cassette insertion at the DBP1 locus is sufficient to cause widespread off-target phenotypes by mis-regulation of Mrp51. These data raised concerns, given the widespread use of expression cassette insertion in genome editing and were consistent with the phenomena of the NGE ( Ben-Shitrit et al, 2012 ; Atias et al, 2016 ; Egorov et al, 2021 ), identified by analysis of deletion collection mutant phenotypes. While these results were disappointing for our study of the function of Dbp1 helicase, they highlighted this locus as a useful context to dissect the mechanism behind, and ideally to fix, these poorly understood cassette-related side effects.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations